Deciphering the Relationship Between Cycloheximides Structures and Their Different Biological Activities - Nguyen, Hang Thi Thu; Kim, Jae Deok; Raj, Vinit; Hwang, In Min; Yu, Nan Hee; Park, Ae Ran; Choi, Jung Seob; Lee, Jintae; Kim, Jin-Cheol (Frontiers in Microbiology, 2021)
Streptomyces species are the most important sources of antibacterial, antifungal, and phytotoxic metabolites. In this study, cycloheximide (CH) and acetoxycycloheximide (ACH) were isolated from the fermentation broth of Streptomyces sp. JCK-6092. The antifungal and phytotoxic activities of the two compounds (CH and ACH) and a cycloheximide derivative, hydroxycycloheximide (HCH), were compared. CH exhibited the strongest antagonistic activity against all the true fungi tested, followed by ACH and HCH. However, both CH and ACH displayed similar mycelial growth inhibitory activities against several phytopathogenic oomycetes, and both were more active than that of HCH. Disparate to antifungal ability, ACH showed the strongest phytotoxic activity against weeds and crops, followed by HCH and CH. ACH caused chlorophyll content loss, leaf electrolytic leakage, and lipid peroxidation in a dose-dependent manner. Its phytotoxicity was stronger than that of glufosinate-ammonium but weaker than that of paraquat in the in vitro experiments. CH and its derivatives are well-known protein synthesis inhibitors; however, the precise differences between their mechanism of action remain undiscovered. A computational study revealed effects of CHs on the protein synthesis of Pythium ultimum (oomycetes), Magnaporthe oryzae (true fungus), and Capsicum annum (plant) and deciphered the differences in their biological activities on different targets. The binding energies and conformation stabilities of each chemical molecule correlated with their biological activities. Thus, molecular docking study supported the experimental results. This is the first comparative study to suggest the ribosomal protein alteration mechanisms of CHs in plants and fungi and to thus show how the protein inhibitory activities of the different derivatives are altered using molecular docking. The correlation of structures features of CHs in respect to bond formation with desired protein was revealed by density functional theory. Overall collective results suggested that CHs can be used as lead molecules in the development of more potent fungicides and herbicides molecules.